From formal to informal: executives who migrated to flexible work - Kim, Han Na; Tonelli, Maria Jose; Silva, Andre Luis (Review of Business Management, 2017)
Purpose: Given the changes occurred in the organization and work, flexible employment contracts are generally associated with a search for more productive employees. The purpose of this research is to understand the behavioural changes needed by executives to face up to the reality of these new flexible models of work. Design/methodology/approach: This paper presents the study that was undertaken in the city of São Paulo (SP - Brazil) with 30 executives who migrated from formal employment contracts – job positions - to more flexible formats. Findings: The results showed that the interviewees use various terms for describing themselves: consultant, independent, franchised, businessperson, councillor, among others, and suggested that they have to change their self-perceptions to be adapted to flexible work. Research implications: This research concerns a topical subject at a time when more people are changing to self-employed status and Brazil is an interesting context for the study. This discussion helps us to understand new dimensions of the global work market. Originality/value: This study shows that the narratives that these executives use to illustrate their professional trajectories are related to how they deal with time, with their network and how they should change their mentality and behaviour in order to achieve success. Lastly these professionals must display competence, even they are sometimes betrayed by their listless gestures, voice and look.